Quality, Coherence and Co-operation:A Framework for Studying the Mediation of Qualities in Food Networks and Collective Marketing Strategies - Noe , Egon; F. Alrøe, Hugo (The International Journal of Sociology of Agriculture and Food, 2011)
The aim of this article is to present an analytical framework to examine how qualities are mediated between producers and consumers, and how this is linked to the way the food chain is constructed, who is involved, and the way the market is developed. The framework is a reorientation to see food networks as consisting of triadic value relations that transform and mediate qualities through the chain, using an analytical typology of quality dimensions. From this perspective, a meta-analysis of case reports from collective farmers’ marketing initiatives in Europe has been performed. The cases differ greatly in the number of quality dimensions involved, and they represent very different strategies to mediate the qualities from field to table. We find that the performance of the marketing strategy is related to coherence in terms of whether the individual value relations are able to carry the involved quality dimensions throughout the whole network. In conclusion, this framework is a promising tool to radicalize our understanding of how qualities are mediated through food networks.